Differential Impact of Single-Dose Fe Ion and X-Ray Irradiation on Endothelial Cell Transcriptomic and Proteomic Responses - Baselet, Bjorn; Azimzadeh, Omid; Erbeldinger, Nadine; Bakshi, Mayur V.; Dettmering, Till; Janssen, Ann; Ktitareva, Svetlana; Lowe, Donna J.; Michaux, Arlette; Quintens, Roel; Raj, Kenneth; Durante, Marco; et al. (Frontiers in Pharmacology, 2017)
Background and Purpose. Radiotherapy is an essential tool for cancer treatment. In order to spare normal tissues and to reduce the risk of normal tissue complications, particle therapy is a method of choice. Although a large part of healthy tissues can be spared due to improved depth dose characteristics, little is known about the biological and molecular mechanisms altered after particle irradiation in healthy tissues. Elucidation of these effects is also required in the context of long term space flights, as particle radiation is the main contributor to the radiation effects observed in space. Endothelial cells, forming the inner layer of all vascular structures, are especially sensitive to irradiation and, if damaged, contribute to radiation-induced cardiovascular disease. Materials and Methods. Transcriptomics, proteomics and cytokine analyses were used to compare the response of endothelial cells irradiated or not with a single 2 Gy dose of X-rays or Fe ions measured one and seven days post-irradiation. To support the observed inflammatory effects, monocyte adhesion on endothelial cells was also assessed. Results. Experimental data indicate time- and radiation quality-dependent changes of the endothelial cell response to irradiation. The irradiation impact was more pronounced and longer lasting for Fe ions than for X-rays. Both radiation qualities decreased the expression of genes involved in cell-cell adhesion and enhanced the expression of proteins involved in caveolar mediated endocytosis signaling. Endothelial inflammation and adhesiveness were increased with X-rays, but decreased after Fe ion exposure. Conclusions. Fe ions induce pro-atherosclerotic processes in endothelial cells that are different in nature and kinetics than those induced by X-rays, highlighting radiation quality-dependent differences which can be linked to the induction and progression of cardiovascular diseases. Our findings give a better understanding of the underlying processes triggered by particle irradiation in endothelial cells, a crucial aspect for the development of protective measures for cancer patients undergoing particle therapy and for astronauts in space.